Tailoring Hydrocarbon Polymers and All‐Hydrocarbon Composites for Circular Economy. Issue 1 (12th November 2018) - Hees, Timo; Zhong, Fan; Stürzel, Markus; Mülhaupt, Rolf
Abstract: The world population will rapidly grow from 7 to 9 billion by 2050 and this will parallel a surging annual plastics consumption from today's 350 million tons to well beyond 1 billion tons. The switch from a linear economy with its throwaway culture to a circular economy with efficient reuse of waste plastics is therefore mandatory. Hydrocarbon polymers, accounting for more than half the world's plastics production, enable closed‐loop recycling and effective product‐stewardship systems. High‐molar‐mass hydrocarbons serve as highly versatile, cost‐, resource‐, eco‐ and energy‐efficient, durable lightweight materials produced by solvent‐free, environmentally benign catalytic olefin polymerization. Nanophase separation and alignment of unentangled hydrocarbon polymers afford 100% recyclable self‐reinforcing all‐hydrocarbon composites without requiring the addition of either alien fibers or hazardous nanoparticles. Recycling of durable hydrocarbons is far superior to biodegradation. The facile thermal degradation enables liquefaction and quantitative recovery of low molar mass hydrocarbon oil and gas. Teamed up with biomass‐to‐liquid and carbon dioxide‐to‐fuel conversions, powered by renewable energy, waste hydrocarbons serve as renewable hydrocarbon feedstocks for the synthesis of high molar mass hydrocarbon materials. Herein, an overview is given on how innovations in catalyst and process technology enable tailoring of advanced recyclable hydrocarbon materials meeting the needs of sustainable development and a circular economy. Abstract : Versatile hydrocarbon materials, tailored in highly energy‐, resource‐, eco‐ and cost‐efficient catalytic olefin polymerization processes, enable the switch from linear to circular economy with efficient reuse of wastes. Nanostructured all‐hydrocarbon composites do not require the use of alien fibers and nanoparticles. As low‐weight and damage‐tolerant hydrocarbon materials, they are readily recycled by repeated remolding and by thermal cleavage into hydrocarbon oil.